Efeito imunomodulador da ouabaína em células de neuroblastoma humano infectadas pelo zika virus - Magalhães, Daniel Wilson Arruda (2024)
Ouabain (OUA) is part of the cardiotonic steroid family and classically acts as an inhibitor of Na+/K+-ATPase. Currently, its immunomodulatory and antiviral activity has been reported in several studies. The Zika virus (ZIKV) is an arbovirus capable of causing neurological disorders; in this context, the dysregulated inflammatory response plays an important role during the neural pathogenesis of the Zika virus (ZIKV). Currently, there are no vaccines or antivirals available to treat the disease caused by ZIKV. Therefore, given the potential of OUA, this study aimed to evaluate its antiviral and anti-inflammatory activity against ZIKV using a human neuroblastoma cell line (SH-SY5Y). Initially, SH-SY5Y cells were treated with different concentrations of OUA to evaluate the cytotoxicity of the substance. Then, after 1 hour of ZIKV infection (multiplicity of infection: 0.1), SH-SY5Y cells were treated with OUA (18 nM), and the concentrations of pro-inflammatory cytokines were determined by enzyme-linked immunosorbent assay (ELISA), and the ZIKV titer was analyzed by TCID50 assay. The production of cytokines in the supernatant of the co-culture between ZIKV-infected SH-SY5Y cells and human macrophages was also evaluated by ELISA. OUA significantly reduced ZIKV-induced interleukin (IL)-6 release (by 25%), tumor necrosis factor (TNF)-α (by 50%), and ZIKV titer (99.9%). In the co-culture, treatment with OUA of ZIKV-infected SH-SY5Y cells significantly reduced IL-1B production by the co-culture. Additionally, intracellular signaling pathways were evaluated by flow cytometry. The results showed that the reduction of IL-6 and TNF-α was accompanied by NF-κB suppression (by 75%), demonstrating the anti-inflammatory activity of OUA during ZIKV infection. In addition, OUA treatment was able to restore the homeostasis of mTOR, ERK, and p38 phosphorylation, highlighting the potential of this molecule in preventing neurogenesis damage caused by ZIKV. Taken together, these data provide the first evidence of the anti-ZIKV and anti-inflammatory activity of OUA against ZIKV infection in a human neuroblastoma cell line. Moreover, this study helps confirm the efficacy of cardiotonic steroids as potential antiviral and immunomodulatory agents, making OUA a promising candidate against ZIKV.